Large‐Sample Evidence on Firms’ Year‐over‐Year MD&A Modifications - BROWN, STEPHEN V.; TUCKER, JENNIFER WU (Journal of Accounting Research, 2011)
ABSTRACT The Securities and Exchange Commission (SEC) has expressed concern about the informativeness of firms’ Management Discussion and Analysis (MD&A) disclosures. A firm's MD&A is potentially uninformative if it does not change appreciably from the previous year after significant economic changes at the firm. We introduce a measure for narrative disclosure—the degree to which the MD&A differs from the previous disclosure—and provide three findings on the usefulness of MD&A disclosure. First, firms with larger economic changes modify the MD&A more than those with smaller economic changes. Second, the magnitude of stock price responses to 10‐K filings is positively associated with the MD&A modification score, but analyst earnings forecast revisions are unassociated with the score, suggesting that investors—but not analysts—use MD&A information. Finally, MD&A modification scores have declined in the past decade even as MD&A disclosures have become longer; the price reaction to MD&A modification scores has also weakened, suggesting a decline in MD&A usefulness.